In situ construction of heterojunctions to regulate the biodegradation behavior of copper carriers for tumor-specific cuproptosis-enhanced sono-immunotherapy - Xiqian Cao; Lingwei Mao; Yijun Tian; Lang Yan; Bijiang Geng; Yingtang Zhou; Jiangbo Zhu (Journal of Nanobiotechnology)
Abstract Cuproptosis, a novel approach utilizing copper carriers to trigger programmed cell death, exhibits promise for enhancing traditional therapies and activating robust adaptive immune responses. However, the uncontrolled release of Cu ions risks triggering cuproptosis in healthy tissues, potentially causing irreversible damage. To address this, we report on the use of a Cu-MOF (copper metal-organic framework) protective layer to regulate the biodegradation of copper-based nanomaterials. In situ formation of Cu-MOF on Cu2O nanocubes not only stabilizes the material under physiological conditions but also enhances its sonodynamic therapy (SDT) capabilities by establishing a Z-Scheme heterojunction. Upon SDT activation, the targeted Cu ion release at the tumor site triggers a cascade of reactions, generating reactive oxygen species (ROS) via Fenton-like processes and depleting glutathione (GSH). This ROS surge, combined with effective cuproptosis, modulates the immunosuppressive tumor microenvironment, inducing immunogenic cell death to eliminate primary tumors and inhibit metastasis. This study offers a new paradigm for the controlled integration of SDT, chemodynamic therapy (CDT), cuproptosis, and immunotherapy, achieving precise tumor-targeted treatment via controlled copper nanomaterial degradation. Graphical abstract